Medial catalexis in Sir Thomas Wyatt’s iambic pentameter - Patrik Bye (Nordlyd: Tromsø University Working Papers on Language & Linguistics, 2021)
There is a reasonable scholarly consensus that the long (“heroic”) line of Sir Thomas Wyatt is an iambic pentameter. However, a significant number of his long lines are apparently syllabically hypometrical, calling into question this interpretation. The doubt is further compounded by Wyatt’s nontrivial use of phrase-medial inversions. I argue that it is nonetheless possible to infer an iambic pentameter intention behind Wyatt’s syllabically hypometrical lines, which can be ‘repaired’ by medial catalexis. Syllabically canonical lines are known to favour major prosodic breaks (Intonational Phrase boundaries) between the second and third foot and, to some extent, between the third and fourth. On the assumption that medial catalexis exploits the natural pauses that occur at the boundaries between Intonational Phrases, what emerges is a significant preference for catalexis to target the weak position of the third verse foot (half-line boundary), followed by the fourth (immediately following the verse-foot adjunct of the second half-line). The finding opens up further possibilities for understanding Wyatt’s other licences, and linguistically informed literary criticism of his verse. The final part of the paper offers some speculations as to the nature of medial catalexis and how it can be approached within a linguistically informed framework compatible with generative metrics.